Efficacy of Short and Mono segment Spinal Fixations in Traumatic Incomplete Thoracolumbar Burst Fractures - Bhattarai, Binod; Shah, Sashi (Journal of College of Medical Sciences-Nepal, 2019)
Background: Controversies still mount over the long segment, short segment and mono segment screw fixation for traumatic thoracolumbar spine burst fractures. This article aims to provide our initial experience of the effectiveness of these management modalities with additive focus on their potential benefits upon preventing the loss of correction over time. Methods: We included all operated cases of thoracolumbar fractures presenting with the ASIA grade of above ‘C’ between December 2014to December 2017 in a retrospective manner in terms of operative time, estimated intra-operative blood loss, any post-operative surgical wound complications, implant cost, average time lapse for the patients to return to physiotherapy and the follow up radiological imaging at 6 months. Results: Long segment fixation is comparatively more time consuming with considerable blood loss and high incidence of postoperative wound complications. We observed that both short as well as mono segment crew fixations had similar incidences with regards to the common complications pertaining to the spinal implant placement procedures. Conclusions: Both short and mono-segment fixation procedures resulted in comparable short and long term results. Though long segment fixation is comparatively more stable, it is, however, expensive with a higher incidence of other postoperative complications.